Hospital building - Wang, Zhi; JTart Publishing & Media ([Guangzhou, China] : JTart Publishing & Media, 2012)
Architectural Design a selection of many foreign design firms. design companies and well-known designer in recent years different aspects of the works of influential medical and architectural design. planning and layout of published cases are from the medical building design. architectural design. structural design. and landscape design for all-round show famous new. Outstanding recent book brings together many of the world's renowned architectural design firm. design master. Aedas. P & T Architects and Engineers Ltd. J.MAYERH. Architectural design companies. Full - covering almost all type of office buildings. administrative office buildings. multi-storey office buildings. high-rise and high-rise office buildings.
Series no. from book jacket.
Keywords: Hospital architecture; Exhibition buildings; Public buildings; Architecture, Modern -- 20th century -- Designs and plans; Architecture, Modern -- 21st century -- Designs and plans